The Effectiveness of Zakat in Breaking the Chain of Poverty (Case Study of Class of 2007 Etos Scholarship Recipients) - Muh Jamil; Syamsu Alam; Andi Samsir; Basri Bado (Universitas Negeri Makassar, 2023)
This research is to analyze the effectiveness of zakat in breaking the chain of poverty in a case study of recipients of the 2007 Etos scholarship in Indonesia. This research focuses on the role of zakat in breaking the chain of poverty. Research data comes from observations and interviews with respondents. Analyzed by descriptive qualitative. The results of the study show that the scholarship program's from zakat funds is able to break the chain of poverty for scholarship recipients.